MENINGKATKAN KETERAMPILAN INKUIRI DAN HASIL BELAJAR IPA MATERI POKOK TEKANAN ZAT MELALUI PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING PADA PESERTA DIDIK KELAS VIII SMPS OIKUMENE KENDARI - rusu, maha; Serlianti, Efi; Kaharudin, La Ode (Universitas Muslim Buton, 2023)
This study aims to describe the increase in inquiry skills and student learning outcomes in science learning the subject matter of substance pressure class VIII SMPS Oikumene Kendari through the application of the guided inquiry learning model This type of research is classroom action research. The research subjects were students of class VIII SMPS Oikumene Kendari who were registered in the even semester of the 2021/202 school year, totaling 29 people. The data collected in this study were data on inquiry skill and student learning outcomes. From the results of data analysis, it was concluded that: 1) the inquiry skills of students in the first cycle were 2.43 in the sufficient category, while in the second cycle, 3.21 were in the good category; 2) the average value of students' learning outcomes in the first cycle obtained an average value of 72.48 with a standard deviation of 12.69, while in the second cycle the average value of student learning outcomes was 78.87 with a standard deviation of 8.32.